Magical Realism in Toshikazu Kawaguchi's Before The Coffee Gets Cold - Vera C Debora; Susanne A.H. Sitohang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study discusses magical realism in Toshikazu Kawaguchi's Before The Coffee Gets Cold. The aims of this study are to find the characteristics of magical realism and to explain the significance of utilizing the magical realism portrayed in the novel. The method applied is descriptive qualitative by presenting dialogues and narration relating to the topics of this study. The results found are that there are five characteristics of magical realism in the novel; 1) the irreducible elements of magic, 2) the phenomenal world, 3) unsettling doubts, 4) merging realms, and 5) the disruption of time. It is also found that the time-travelling and the ghost presented in the novel are significant for utilizing magical realism to explore and understand reality from a different point of view as well as to criticize perceived, knowable reality. keywords: magical realism, ghost, Japan